How Social Scientists Make Causal Claims in Court: Evidence from the L'Aquila Trial. (May 2017) - Brandmayr, Federico
This paper contributes to two topics that have received insufficient attention in science and technology studies: the social dimensions of causal reasoning and how the knowledge-making site of expert testimony affects the production and reception of social scientific knowledge. It deals with how social scientists make causal claims when testifying as expert witnesses in trials where causal claims are relevant, using as a case study the so-called L'Aquila trial, in which experts were summoned by the parties to testify on the causes of risk-related behavior by the inhabitants of an Italian city in early 2009. In particular, I analyze the process of selection of causal loci, the attribution and removal of agency, the increase and decrease of causal factors in the explanation of an event, and the delimitation of the explanandum. As a general insight derived from the case, it is argued that the position of experts in a trial––which side summons them––may be a more important factor than their branch of expertise to account for certain types of these practices.